Protection of Child Health in Emergencies - Övgü Büke; Nalan Karabayır (AVES Yayincilik, 2024)
Natural disasters present a significant and growing threat to the well-being of children. Every year 175 million children globally are expected to be affected by natural disasters, including floods, cyclones, droughts, heatwaves, severe storms, and earthquakes. In emergencies, children of all age groups, especially those under 5, are the most affected part of the community, with child mortality rates 2-70 times higher than average. Clean water, sanitation and hygiene measures, vaccination to prevent infectious diseases, providing psychological support to vulnerable children in an age-appropriate approach, and paying particular attention to children with special needs are extremely important. Healthcare personnel and families should have adequate information and preparation to do what is necessary before, during, and after emergencies to minimize the negative effects on children. In this review, we aim to discuss the effects of emergencies on children and the prevention methods.